Vocabulary in English in Tertiary Contexts: Connecting Research and Learning - Coxhead, Averil (LEARN Journal: Language Education and Acquisition Research Network, 2021)
Knowledge of vocabulary is essential for learners of any language, and unfortunately, it has become clear recently the learners of English in a variety of contexts have not scored well on vocabulary tests. Low scores are problematic for language use and success in general, but they cause particular problems when it comes to the vocabulary needed in English in tertiary contexts. This article focuses on vocabulary in English for university purposes by reflecting on recent research and how its impact and connection to learning and teaching. The article focuses on six main areas of research: knowledge of vocabulary, the amount of vocabulary learners need for studying at university, frequency and vocabulary, English for General Academic Purposes (EGAP) and English for Specific Academic Purposes (EGSP) in connection with word lists, and testing, academic multiword units, and finally, word parts in academic vocabulary. These areas all shed light on different aspects of academic vocabulary, and illustrate some of the depth and commitment to this fast moving area of research over the last two decades.